Early surgical intervention may facilitate recovery of cervical spinal cord injury in DISH. (18th March 2019) - Tsuji, Osahiko; Suda, Kota; Takahata, Masahiko; Matsumoto-Harmon, Satoko; Komatsu, Miki; Menjo, Yusuke; Watanabe, Kota; Ishii, Ken; Nakamura, Masaya; Matsumoto, Morio; Minami, Akio; Iwasaki, Norimasa
Study design: A retrospective study of consecutive surgically managed cases of cervical spinal fractures and diffuse idiopathic skeletal hyperostosis (DISH) at our hospital from October 2006 to April 2016. Summary of background data: Prognostic factors have not been determined for cervical fractures in DISH. Objectives: To assess demographics, surgical techniques, and complications in cervical spinal cord injury with DISH and to evaluate factors affecting neurological prognosis. Methods: Patients' medical records and radiographs were reviewed and analyzed for demographics, injury characteristics, surgical outcomes, perioperative complications, additional surgeries, and neurological prognosis. Neurological status was assessed by the American Spinal Injury Association (ASIA) grade at admission and discharge. Results: Of 38 patients (mean age 71.9 ± 8.8), 20 had type 1 fractures (through the disc space), 8 had type 2 (through the vertebral body), and 10 had type 3 (through disc and vertebral body). ASIA grades at admission included 14 ASIA-A, 4 ASIA-B, 7 ASIA-C, 8 ASIA-D, and 5 ASIA-E. All patients underwent posterior fusion with an average of 4.5 ± 2.5 instrumented vertebrae (range, 2–7) and six patients required secondary halo-vest fixation. Of 14 ASIA-A patients, 12 developed serious postsurgical pulmonary complications and 4 of these died within 6 months of surgery. Of the 38 patients, 13 improved more than one grade after treatment, 24 did not improve, and 1 deteriorated. In the 18 ASIA-A/B cases (complete motor paralysis), neither fracture type nor injury mechanism (e.g. a ground-level fall or high-energy trauma) correlated with neurological prognosis, but a time of 8 h or less from injury to surgery correlated significantly with an improvement from ASIA A/B to C/D ( p < 0.01, Pearson's χ 2 test). Conclusion: Patients with complete motor paralysis after a cervical fracture with DISH may recover to partial paralysis if surgically treated within 8 h of injury.